Government by mourning : death and political integration in Japan, 1603-1912 - Hirai, Atsuko (Harvard East Asian monographs ;, 2014)
"Hirai reveals how the decrees on mourning played an important integrative part in the Tokugawa period through not only its comprehensive implementation, especially among major political figures, but also its codification of the religious beliefs and customs that the Japanese people had cherished for innumerable generations"--Provided by publisher